Accurate Identification of Degraded Products of Aflatoxin B1 Under UV Irradiation Based on UPLC-Q-TOF-MS/MS and NMR Analysis - Wang, Yan-Duo; Song, Cheng-Gang; Yang, Jian; Zhou, Tao; Zhao, Yu-Yang; Qin, Jian-Chun; Guo, Lan-Ping; Ding, Gang (Frontiers in Chemistry, 2021)
Analysis, purification, and characterization of AFB1 degraded products are vital steps for elucidation of the photocatalytic mechanism. In this report, the UPLC-Q-TOF-MS/MS technique was first coupled with purification and NMR spectral approaches to analyze and characterize degraded products of AFB1 photocatalyzed under UV irradiation. A total of seventeen degraded products were characterized based on the UPLC-Q-TOF-MS/MS analysis, in which seven ones (1–7) including four (stereo) isomers (1,2, 5, and 6) were purified and elucidated by NMR experiments. According to the structural features of AFB1 and degraded products (1–7), the possible photocatalytic mechanisms were suggested. Furthermore, AFB1 and degraded products (1–7) were evaluated against different cell lines. The results indicated that the UPLC-Q-TOF-MS/MS technique combined with purification, NMR spectral experiments, and biological tests was an applicable integrated approach for analysis, characterization, and toxic evaluation of degraded products of AFB1, which could be used to evaluate other mycotoxin degradation processes.